The effect of sound absorption by the air on noise propagation - K. BEREZOWSKA-APOLINARSKA; J. JARZĘCKI; R. MAKAREWICZ (Archives of Acoustics)
In this paper, the relationship between the sound level (measured in dB(A)) and the distance was derived on the assumption that air absorption is the only essential factor affecting noise propagation. It was shown that at a great distance from the source "rapid sound level drop", exceeding 6 dB(A), occurs when the distance is doubled.